Case report: Discovery of tuberculosis caused by Mycobacterium bovis in free-ranging vervet monkeys in the Greater Kruger Conservation Area - de Klerk-Lorist, Lin-Mari; Miller, Michele A.; Mitchell, Emily P.; Lorist, Rudolf; van Dyk, D. Schalk; Mathebula, Nomkosi; Goosen, Louise; Dwyer-Leonard, Rebecca; Ghielmetti, Giovanni; Streicher, Elizabeth M.; Kerr, Tanya J. (Frontiers in Veterinary Science, 2024)
Animal tuberculosis (TB) has been reported in several wildlife species in the Greater Kruger Conservation Area (GKCA), South Africa. This report describes the discovery of clinical tuberculosis, caused by Mycobacterium bovis (M. bovis), in free-ranging vervet monkeys (Chlorocebus pygerythrus). The “One Health” concept is especially relevant to TB since this is a multi-host disease with zoonotic potential and is endemic in GKCA. Vervet monkeys have become habituated to humans in tourist areas and may be a source of infection through close contact. Indirect transmission of M. bovis through environmental sources has also been suspected to present a risk of spread between host species. Clinically diseased monkeys present in two tourist areas in the GKCA, that died (n = 1) or were euthanized (n = 5), were submitted for diagnostic necropsies. The presence of pathological lesions, Ziehl-Neelsen-stained impression smears, Xpert® MTB/RIF Ultra (GXU) assay, mycobacterial culture and speciation by genomic regions of difference PCR, were used to confirm the diagnosis of M. bovis infection in these monkeys. The finding of multiple cases necessitates further investigation of TB in monkey troops living within the GKCA tourist areas to determine the source of infection and assess the risk of transmission to other animals and humans.